Assisted reality device to guide cardiac implantable device programming in distant rural areas. (22nd January 2023) - Diaz, Juan C.; Cañas, Felipe; Duque, Mauricio; Aristizabal, Julian; Niño, Cesar; Bastidas, Oriana; Marin, Jorge; Rivera, Estefania; Hoyos, Carolina; Matos, Carlos; Peralta, Adelqui; Martin, David T.; et al.
Abstract: Background: Patients with cardiac implantable electronic devices (CIEDs) living in rural areas have difficulty obtaining follow‐up visits for device interrogation and programming in specialized healthcare facilities. Objective: To describe the use of an assisted reality device designed to provide front‐line workers with real‐time online support from a remotely located specialist (Realwear HTM‐1; Realwear) during CIED assistance in distant rural areas. Methods: This is a prospective study of patients requiring CIED interrogation using the Realwear HMT‐1 in a remote rural population in Colombia between April 2021 and June 2022. CIED interrogation and device programming were performed by a general practitioner and guided by a cardiac electrophysiologist. Non‐CIED‐related medical interventions were allowed and analyzed. The primary objective was to determine the incidence of clinically significant CIED alerts. Secondary objectives were the changes medical interventions used to treat the events found in the device interrogations regarding non‐CIED related conditions. Results: A total of 205 CIED interrogations were performed on 139 patients (age 69 ± 14 years; 54% female). Clinically significant CIED alerts were reported in 42% of CIED interrogations, consisting of the detection of significant arrhythmias (35%), lead malfunction (3%), and device in elective replacement interval (3.9%). Oral anticoagulation was initiated in 8% of patients and general medical/cardiac interventions unrelated to the CIED were performed in 52% of CIED encounters. Conclusion: Remote assistance using a commercially available assisted reality device has the potential to provide specialized healthcare to patients in difficult‐to‐reach areas, overcoming current difficulties associated with RM, including the inability to change device programming. Additionally, these interactions provided care beyond CIED‐related interventions, thus delivering significant social and clinical impact to remote rural populations. Abstract : In this study, the use of an assisted reality device allowed for successful interrogation of CIED's in a remote, rural population. Device interrogation was performed by a GP guided by a remotely located EP. A significant proportion of patients had clinically significant CIED events, as well as changes in their medical treatment for non‐CIED related conditions highlighting the significant social impact such an intervention can have in underserved communities.